Fabrication and properties of lightweight SiOC modified carbon-bonded carbon fiber composites. Issue 9 (July 2016) - Niu, Min; Wang, Hongjie; Su, Lei; Zhang, Dahai; Shi, Jianjun
Abstract: SiOC modified carbon-bonded carbon fiber composites (CBCFs) with densities of 0.38, 0.61, 0.94 g cm −3 were prepared by precursor infiltration and pyrolysis method using dimethoxydimethylsilane and methyltrimethoxysilane as precursors. The densification behavior was investigated by analyzing the microstructure of CBCF-SiOC (CS) composites with different densities. The mechanical properties and oxidation resistance of the CS composites were studied. Results indicate that the CS composites with the density of 0.94 g cm −3 exhibit better mechanical and anti-oxidation properties.